Development of motor activity of high school students by means of basketball - Tretyakov A.S. ,; Loginov D.V. ,; Lozovoy A.A. ,; Lozovaya M.A. , (Theory and Practice of Physical Culture, 2023)
Objective of the study was to prove the influence of sports games on the development of motor activity of students aged 14–16 years. Methods and structure of the study. The proposed program was as follows: participants in the experiment were offered a set of exercises from the lesson system, aimed at developing motor activity through special basketball exercises and playing basketball. A series of notes on experimental lessons was developed and compiled taking into account the regulations governing the activities of secondary schools, in accordance with the main regulatory documents in the field of education of the Russian Federation, as well as on the basis of sample programs for children's and youth sports schools. Results and conclusions. The use of our proposed methodology using the means of the sports game “basketball” turned out to be effective in the development of motor activity of schoolchildren. It was revealed that with the help of the sports game “basketball” one can effectively develop motor activity, which underlies the physical development of students. In the course of our work, we proved that using the developed methodology, the degree of development of motor activity in students increased. Consequently, this technique can be used when teaching students aged 14–16 years in the classroom, as well as when preparing young basketball players.